Bathymetric Controls on Rotational Surfzone Currents. Issue 6 (15th June 2018) - McCarroll, R. Jak; Brander, Robert W.; Scott, Tim; Castelle, Bruno
Abstract: A multibeach Lagrangian data set was used to determine bathymetric controls on flow variability within the surfzone. Seven microtidal flow regimes were examined, six containing rip channels, under moderate shore normal waves. Three selected zones exemplified varying bathymetric control: (i) a alongshore uniform zone; (ii) a shallow rip channel at an oblique angle to shore normal; and (iii) a deep, shore‐normal rip channel. Bathymetric variables included alongshore nonuniformity ( φ ) and channel angle relative to shore normal ( α ). Low‐frequency flow (0.01 Hz) was described by velocity ( U ), velocity standard deviation ( σ U ), angular deviation ( σ θ ), and bias in direction of eddy rotation ( ζ bias ). Observations of the exemplar zones indicated the following: (i) near‐zero mean flow with transient eddies within the alongshore uniform zone; (ii) low mean flow with high ζ bias within the oblique channel; and (iii) strong mean flow with low ζ bias in the deep channel. Bathymetry and flow variables were spatially averaged and linearly correlated, scaling for wave forcing. Normalized flow variables were found to be interdependent and were correlated with bathymetric variability, with [ U  ∝  φ ], [( U / σ U ) ∝  φ ], and [ σ θ  ∝  −  φ ], all with ( R 2  ≥ 0.8). A correlation was determined between α and ζ bias ( R 2  ≥ 0.7, increasing as zone width is decreased), with peak ζ bias within oblique channels. Based on these results, a conceptual model is introduced to predict flow behavior for known bathymetry. Surfzone currents were found to span a dynamic continuum from transient eddies on alongshore uniform bathymetry, to channelized rip currents, forced by bathymetric three‐dimensionality and mediated by channel geometry. Key Points: Lagrangian data across seven flow regimes used to determine how bathymetric variations affect flow behavior within the surfzone Bathymetric variability correlated with mean velocity, and inversely with directional variability, channel angle controls eddy direction Flow continuum found from alongshore uniform morphology transient eddies, to rip channeled mean currents, modulated by channel geometry